The importance of negotiating for improved information systems delivery - Sirinidis, Georgia (My University, 2006)
Interpersonal Conflict is a neglected topic in Information System Development (ISD). While deemed important, few ISD studies have examined interpersonal conflict, the management of this conflict, or the impact this conflict has on project outcomes. Research in this field has revealed that conflict between different user groups within the systems development team is considered to be a significant threat to the success of a project. Failed systems have been attributed to resistance to system change, political issues that arise as a result of the system change and poor qua lity of teamwork between users and technical staff, analysts, programmers and other IS professionals and cultural differences. Better methods of systems analysis and design are thus needed to ensure appropriate, feasible and acceptable programs and applications and it is therefore with this intention, that this dissertation is submitted: to consider organisational behavioural means, in particular the importance of negotiating within the Systems Development process, to improve systems development. There were multiple objectives to this dissertation. These were: · to investigate whether system development is currently experienced as a process of conflict · to ascertain which roles experience a greater degree of conflict · to ascertain which systems development life cycle (SDLC) and which methodologies experience a greater degree of conflict · to assess whether negotiating skills vary across the different roles within the SDLC, to assess whether negotiating skills vary across SDLC methodologies · to determine whether the interest to improve negotiating skills varies within the SDLC · to evaluate the importance attached to negotiating skills in the SDLC · to assess whether the acceptance of the proposed negotiating framework for systems development varies within the SDLC · to examine what factors play a role in the acceptance of the proposed frameworks and · to assess whether the proposed framework will improve systems delivery. ii The reach of the research was limited to organisations in Southern Africa. These organisations were either large software development houses, or small IT departments within organisations, which specialised in developing either outsourced systems or in- house systems. Selfadministered questionnaires were mailed out to system development teams in South Africa, of varying industries and a total sample of one hundred and fifty five respondents replied. A quantitative approach was adopted to analyse the data. The results of the research show that minimal conflict is currently experienced in the SDLC and respondents across all roles and methodologies feel they possess negotiation skills to handle the conflict. The majority of the sample favourably accepted the proposed framework. Some roles attached more importance to the need for negotiating skills in their line of work, and paid more attention to improving their negotiating skills than others.
Faculty of Information Systems School of Economic and Business Sciences 9406128v georgia.sirinidis@fnbcorporate.co.za
Keywords: Negotiating; Soft systems; SDLC; Communication Skills; Improved Systems Projects